Economic Analysis of Regional Distributed Energy System Bidding for Accessing to the Grid. (June 2016) - Qiu, Liuliang; Ren, Hongbo; Wu, Qiong
Abstract: This paper focuses on the subject of HDE and near OPEU in shanghai, compares the economic under the system of DE grid-connected with no power injection at present and bidding for accessing to networks after electric power reform. After the reform, HDE could recycles corresponding operating and maintenance costs by sharing power generation benefits, OPEU could save the electricity purchasing fund obviously. It is shown that the electric power reform program will help to stimulate the vitality of DE market, escort China's regional DE healthy and rapid development.